A collaborative system to improve knowledge sharing in scientific research projects. (September 2019) - Julpisit, Attipa; Esichaikul, Vatcharaporn
As knowledge sharing is important for every sector, it should be encouraged among team members. Particularly, scientific research projects usually involve knowledge-intensive teams that require members to share various knowledge forms while working together. Although several collaborative systems exist on different platforms, the system features required to improve knowledge sharing between researchers are insufficient. A collaborative system, the Research Collaboration System, designed and developed based on identified collaborative activities and the SECI model, is evaluated by two scientific research projects. Preliminary results show that this system could serve all major research activities of scientific research projects and enhance knowledge sharing.